Does restored plant diversity play a role in the reproductive functionality of Banksia populations? - Ritchie, A.; Nevill, Paul; Sinclair, E.; Krauss, S. (Blackwell Science Inc., 2016)
Vegetation structure and plant species diversity of restoration sites are predicted to directly affect pollinator attraction, with potential impacts on gene flow, reproduction, genetic diversity of future generations, and ultimately restoration success. We compared Banksia attenuata R.Br. (Proteaceae) in a low species diversity restoration site and an adjacent natural remnant. We assessed fecundity genetic diversity in adult plants and their offspring, mating system parameters and pollen dispersal using paternity assignment. Results were compared to an earlier study of reproductive functionality within a high species diversity restoration site that was restored in a similar manner, enabling us to investigate any association between plant species diversity and fecundity. Seed set data indicated no significant differences between restored and adjacent natural sites; however, seed set data between restoration sites was significantly different (2.08 ± 0.39 and 6.89 ± 1.12, respectively). The mean number of fruits (follicles) per inflorescence was not significantly different between restoration sites. Genetic diversity of adult plants and their offspring were comparable in all sites. Higher allelic richness and genetic differentiation in one restored site reflected sourcing beyond local provenance. Low correlated paternity indicated high levels of multiple siring of seeds and paternity assignment demonstrated strong genetic connectivity between sites. Reproductive functionality, as measured by fecundity and genetic diversity in the offspring of B. attenuata, is resilient to low species diversity within a restored plant community. We consider our results in the context of establishing seed production areas (SPAs) that maximize the quantity and genetic quality of Banksia seeds for restoration.